Acceleration of cervical cancer diagnosis with human papillomavirus testing below age 30: Observational study. Issue 9 (31st December 2021) - Rebolj, Matejka; Mathews, Christopher S.; Pesola, Francesca; Castañon, Alejandra; Kitchener, Henry; ,
Abstract: Several international cervical screening guidelines advise against using high‐risk human papillomavirus (HR‐HPV) testing in women younger than 30. The rationale for this in young women, lies in the potential for additional detection of both low‐grade and high‐grade cervical intraepithelial neoplasia (CIN) leading to unnecessary treatments without reducing the burden of cervical cancer. We studied 56 544 women screened at 24 to 29 with HR‐HPV testing and 116 858 screened with liquid‐based cytology (LBC) in the English HPV screening pilot. They were compared to 528 460 women screened at the age of 30 to 49. We studied the detection of cervical cancer and CIN2/3 across two consecutive screening rounds 3 years apart. At 24 to 29, a positive HR‐HPV test detected more cases of cervical cancer in the prevalence round than did a positive LBC test (1.36/1000 screened vs 0.82/1000, ORadj : 1.61, 95% CI: 1.18‐2.19). In women with a negative HR‐HPV test, cervical cancer was diagnosed before or at the incidence round in 0.07/1000. After a negative LBC test, cancer detection reached 0.47/1000 and 40% of these cases were diagnosed at FIGO stage IB+. HR‐HPV testing increased the detection of CIN2/3 diagnoses in two consecutive rounds combined by 30% (71.9/1000 vs 55.2/1000). The patterns of detection of cervical cancer and CIN2/3 were almost identical at older ages. These data support using HR‐HPV testing for screening of women younger than 30, which not only accelerates the diagnosis of cervical cancer but leads to a similar relative increase in CIN2/3 diagnosis to that found in women aged 30 to 49. Abstract : What's new? The new data from this large population‐based study convincingly demonstrate that HPV testing as a stand‐alone cervical screening test, can accelerate the diagnosis of cervical cancer compared with liquid‐based cytology. Using our protocol this was achieved while maintaining the increased detection of CIN2/3 at a level similar to that seen in women screened age 30‐49. These results should stimulate policy makers to re‐consider HPV testing below age 30.